Analysis of Factors Determining Patient Preferences in Primary Healthcare: a Choice Modeling Study Using Conjoint Analysis on the Market Positioning Strategy of Independent Clinic (Pusat Riset dan Inovasi Nasional, 2024)
The primary objective of this study is to quantify the relative importance of key service attributes driving patient choice and to formulate an evidence-based turnaround strategy. The research hypothesizes that while cost is a factor, specific segments may value continuity of care over facilities (Hypothesis 1) and that employment status significantly alters time sensitivity (Hypothesis 3). To achieve these objectives, the study employs a quantitative approach using Choice-Based Conjoint (CBC) analysis. Primary data were collected from 107 respondents, consisting of women of reproductive age or a husbands in the Bandung area. The data were analysed using Hierarchical Bayes (HB) estimation to derive individual-level part-worth utilities, followed by market simulations to predict the share of preference under various competitive scenarios. The empirical results reveal a market reality that contradicts traditional assumptions. The analysis identifies Cost of Service (38.2%) and Clinic Facilities (17.8%) as the dominant drivers of choice. Contrary to the assumption that midwifery patients prioritize personal relationships, the study finds that the